Dispersion and Aging of Volcanic Aerosols After the La Soufrière Eruption in April 2021. Issue 8 (19th April 2023) - Bruckert, J.; Hirsch, L.; Horváth, Á.; Kahn, R. A.; Kölling, T.; Muser, L. O.; Timmreck, C.; Vogel, H.; Wallis, S.; Hoshyaripour, G. A.
Abstract: Volcanic aerosols change the atmospheric composition and thereby affect weather and climate. Aerosol dynamic processes such as nucleation, condensation, and coagulation modify the shape, size, and mass of aerosol particles, which influence their atmospheric lifetime and radiative properties. Nevertheless, most models omit these processes for ash particles. In this work, we explore the ash aerosol aging and sulfate production during the first 4 days following the 2021 La Soufrière (St. Vincent) eruption with the ICON‐ART model (ICOsahedral Nonhydrostatic model with Aerosol and Reactive Trace gases). Online coupling of ICON‐ART with a one‐dimensional volcanic plume model calculates volcanic emission, which makes it possible to resolve the different eruption phases of the noncontinuous La Soufrière eruption. We compared our simulated aerosol distribution and composition with observations from the Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) instrument, the Multiangle Imaging SpectroRadiometer (MISR) Research Aerosol (RA) Algorithm, and the Barbados Cloud Observatory (BCO). We show that online coupling is essential to adequately model the emissions and plume development close to the volcano. The modeled aerosol aging is in very good agreement with observations from MISR near the emission source and with CALIOP at larger distances. Furthermore, particle aging occurs faster in the troposphere than in the stratosphere due to the availability of water vapor and OH, but a layer of coated ash appears at the plume top due to faster oxidation of SO2 and lofting by aerosol‐radiation interaction. This paper gives the first direct comparison of aerosol aging in volcanic eruption plumes between simulations and observations. Plain Language Summary: Large volcanic eruptions can influence weather and climate, and endanger aviation and public health. To constrain these effects and risks, it is critical to reliably predict the volcanic plume dispersion. However, the atmospheric lifetime of the ash released during an eruption is influenced by many factors, such as emission height, meteorology, and aerosol dynamical processes. Aerosol dynamical processes lead to growth and aging of volcanic plume particles. They include the formation of new particles from precursor gases, condensation on existing particles, and coagulation of particles. This paper investigates the formation of aged ash particles in model simulations and observations following the 2021 La Soufrière eruption. We consider ash aging both close to the volcano and during further transport. We found that ash aging takes place already close to the volcano and the fraction of aged particles increases with distance from the source. During further transport, a layer of aged ash particles forms at the plume top due to interaction of these particles with radiation and subsequent warming of the plume. Key Points: Resolving individual eruption phases is essential for modeling the 2021 La Soufrière eruption Combination of modeling and satellite data confirm, for the first time, the aging of volcanic ash Ash aging and sulfate production rates depend on distance from the source and altitude